Medial temporal lobe encodes cognitive maps of real-world social networks - Yi Yang Teoh; Jae-Young Son; Alice Xia; Apoorva Bhandari; Oriel FeldmanHall (Proceedings of the National Academy of Sciences, 2026)
Humans routinely solve social problems by navigating densely interconnected networks—gossiping strategically, brokering across cliques, and coordinating with allies. Yet, the neural representations supporting such complex navigation remain undocumented, leaving a crucial gap in our understanding of the mechanisms underlying flexible social cognition. We combine computational modeling with fMRI and a longitudinal measurement of a large, real-world social network (N = 187) to show that the medial temporal lobe encodes an abstract cognitive map of long-range connectivity in the broader network. These neural maps specifically encode the Katz communicability between network members, not merely direct ties, or Euclidean or graph distance. We additionally find that the availability of these maps in the right entorhinal cortex (rEC) and right anterior hippocampus (raHC) supports accurate inferences about information diffusion through the network. Finally, we link neural representation to consequential social change, finding that stronger rEC encoding predicts real-world brokerage that increases community cohesion over time. Together, these findings advance a general mechanism for how the brain supports flexible behavior in complex social environments, closing a major gap between theories of cognitive maps and the demands of social navigation.